PRELIMINARY STUDIES ON FREEZING CHARACTERISTICS OF BOMBAY DUCK(HARPODON NEHEUS) - RADHAKRJSHNAN, A. G. RADHAKRJSHNAN G; SOLANKI, K K; VENKATARMAN, R (Fishery Technology, 2016)
Fresh Bombay duck (Harpodon nehereus) can be quick -frozenat -40°C. and stored at -l0°F. for about 3 months in a very fairand acceptable condition. The maximum drip loss observed wasabout 24%. Rapid· dectea:se :i.n the extractable protein nitrogen ofthe fish muscle was noted during the frozen storage.